Effect of glucosamine supplementation on performance and egg quality of laying chicken - M K, TRIPATHI; R K, KAMAL; RAJNI, KUMARI; R K, RAMAN; P K, RAY; P C, CHANDRAN; S, DAYAL; A, DEY; K, SARMA (The Indian Journal of Animal Sciences, 2025)
The experiment was conducted to explore the effect of supplemental glucosamine on egg production and quality performance of Vanaraja Chickens. The chickens of same age (8 week) were divided into three equal groups i.e. Control (C), Group 10, and Group 20. Birds in group G10 and G20 were supplemented with glucosamine hydrochloride @ doses of 10 mg/kg and 20 mg/kg of body weight/day respectively, via drinking water individually in a plastic container kept in cages. The amount of the supplemented glucosamine was based on their body weight taken fortnightly. The effect of glucosamine on laying performance of the treated groups was compared with control group. For hormonal estimation, blood samples were collected at 15 weeks and 22 weeks of age. Data were analysed using ANOVA (Analysis of Variance) and paired t-test. It was found that the age at first egg laying (AFE) was lesser in G10 and G20 as compared to control group. Egg production was highest in the G10 group based on initial six month records. There was no significant difference of glucosamine supplementation in the important quality parameters including egg weight, shell weight, shell thickness, yolk weight and albumin weight. There was significant increase in the plasma estrogen and leptin level between 15 weeks and 22 weeks of age in all the three groups indicating their role in attaining puberty. Our results indicate that glucosamine hydrochloride may have role in egg laying performance in poultry.